Dynamics and Challenges of Business Communication in the Era of Digital Disruption - M Leo Febriansyah; M Fahri Ramadhan; M Lucky Antoni; Ibnu Agung Hermawan; M Abdu Fahmi; Havis Aravik (Penerbit dan Percetakan CV. Picmotiv, 2026)
The era of digital disruption has brought significant changes to various aspects of business, particularly in business communication practices. The development of digital technology is driving a shift from conventional communication to faster, more interactive, and open digital-based communication. This study aims to analyze the dynamics of business communication in the era of digital disruption and identify the various challenges faced by organizations. The method used is a qualitative approach with desk research, through data collection from various sources such as scientific journals, books, and previous research. The results show that digital technology plays a significant role in increasing the effectiveness of business communication through the speed of information, the integration of various communication channels, and the ability to personalize messages. However, several challenges remain, including high information flow, the risk of miscommunication, the rapid spread of negative information, and changes in consumer behavior that are increasingly active and critical. Therefore, an adaptive, integrated, and technology-based business communication strategy is needed so that organizations can face challenges and capitalize on opportunities in the era of digital disruption.